Laboratory study on the effects of hydro kinetic turbines on hydrodynamics and sediment dynamics. (December 2018) - Ramírez-Mendoza, R.; Amoudry, L.O.; Thorne, P.D.; Cooke, R.D.; McLelland, S.J.; Jordan, L.B.; Simmons, S.M.; Parsons, D.R.; Murdoch, L.
Abstract: The need for hydrokinetic turbine wake characterisation and their environmental impact has led to a number of studies. However, a small number of them have taken into account mobile sediment bed effects. The aim of the present work is to study the impact of the presence of a horizontal-axis three-bladed turbine with the flow and a mobile sediment bed. We use a series of laboratory experiments with a scaled modelled turbine installed in a flume with a mobile sandy bed at the bottom. Acoustic instruments were used to monitor flow, suspended sediment and bed behaviour. Results show a velocity decrease of about 50% throughout the water column and no flow recovery after a distance of 15 rotor diameters. Clearly visible ripples in the absence of the model turbine were replaced by horseshoe-shaped scour pit in the near wake region, and a depositional heap in the far wake. Suspended sediment differences were recorded in the streamwise direction with a possible effect of the wake as far as 15 rotor diameters. These results imply potentially important effects on the efficiency of turbine arrays, if the flow were to be lower than expected, on turbine foundations and modify coastal sediment transport. Highlights: The relationship between a modelled turbine, flow and sediments is investigated. A velocity decrease of about 50% was found in the presence of the rotor. No flow recovery was recorded after a distance of 15 diameters from the rotor. A horse-shoe shape scour pit was developed in the near wake region. Suspended sediment patterns were affected as far as 15 diameters from the rotor.